Underground infrastructures planning, design, and construction - Goel, R.K (Butterworth-Heinemann, 2012)
Offers exposition of the classification of underground space, important considerations such as geological and engineering and underground planning. This title includes chapters concerning applications for underground water storage, underground car parks, underground metros and road tunnels and underground storage of crude oil, lpg and natural gas.